Increasing Interest and Learning Outcomes Based on Student Learning Character Using ASSURE Learning Design in Geography Learning - Eko Hariyadi; ST Norma; Nasarudin Nasarudin; Samsi Awal; Erfina Erfina; Ahmad Iskandar (JURNAL PENDIDIKAN IPS, 2025)
This study aims to improve students' interest and learning outcomes based on students' learning characteristics using ASSURE model learning design in geography class XI-4 SMAN 1 Watubangga Kabupaten Kolaka. The research method uses a class action research design (PTK), data is collected using observation techniques, questionnaires, and tests and the data is analyzed descriptively quantitatively. The results of the study concluded that there was an increase in interest in learning seen based on indicators of interest in learning, in the indicator of attention to learning increased from 61.83% to 79.46%, then the indicator of student interest with a percentage of 65.84% to 80.35%, in the third indicator the feeling of pleasure had a percentage of 64.5% to 80.35%, and the fourth indicator, namely active in learning, also increased with a percentage of 62.27% to 80.58%. Likewise, students' learning outcomes have increased where the average score in cycle 1 was 67 to 81 in cycle 2 with a percentage of classical completeness of 46% in cycle 1 to 86% in cycle 2. The results of this study indicate that the application of ASSURE learning model designed based on students' learning characteristics can improve students' interest and learning outcomes in geography learning.